MEMBANGKITKAN KEPERCAYAAN DIRI PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA MELALUI STRATEGI EVERYONE IS A TEACHER HERE PADA MATERI PROGRAM LINEAR DI SMAN 5 PINRANG - Dewi Anggreni; Buhaerah; Usman (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
The purposed of this study were: (1) determine the self-confidence of students in class XI at SMAN 5 Pinrang; (2) determine learning mathematics through the everyone is a teacher here strategy in class XI at SMAN 5 Pinrang; and (3) determine the everyone is a teacher here strategy can generate confidence students of class XI in learning mathematics in the Linear Program material at SMAN 5 Pinrang. The type of this research was pre-experimental research with data collection instruments using learning implementation observation sheets, student activity observation sheets, and questionnaire sheets. The data analysis technique wa using descriptive analysis and non-parametric statistical analysis with the Wilcoxon formula. Wilcoxon test results obtained Zcount = 4.847 and Ztable = 1.96 so that Zcount > Ztable. Thus, H1 is accepted and H0 is rejected. So the research shows that students' self-confidence can be raised through the everyone is a teacher here strategy. This was indicated by (1) the activities of students in accordance with learning through the everyone is a teacher here strategy increased because the percentage that met the aspects > 70%; (2) the percentage value of the implementation of learning was 72.2% and included in the